SUSTAINABLE DEVELOPMENT AND THE FUTURE GENERATIONS - Kemi Anthony Emina (Social Sciences, Humanities and Education Journal, 2021)
Due to the increasing rate of human’s economic activity and rapid population growth, twenty first century has seen an unprecedented environmental change. These changes have an unprecedented impact on climate, life-sustaining systems on the earth. Future generations are exposed to great harm by the way in which humans exploit environmental resources of the earth. There is a call among environmental ethicists to review human ethical relationship with the environment as to attain sustainable development for the now and the future generations. Hence, the essence of this paper is to discuss the anthropoholistic environmental ethics, sustainable development and the future Generations. This paper argues that humans need to strive for a new and more respectful relationship with the natural environment in other to attain sustainable development. Also, human obligations towards sustainable development for the future must find a firm basis in social ethics: those obligations have to do with our conception of a just society.